When Women Are in Charge: The Language Japanese Women Speak at Work - Dubuc, Claude-Eve (Anthropologica, 2012)
Though in percentages still very few, women active in socially high and powerful positions are now an undeniable part of the Japanese public sphere. In the business context, these women make linguistic choices prompted by the necessity to perform in their roles as professionals and act as legitimate members of society. The resulting linguistic behaviour is reveal ing of their personal experiences, as well as of socio-cultural norms and expectations. Using analysis from fieldwork in To kyo, the present article shows the importance of focusing not only on so-called Japanese women's language but also on the way women speak in Japan today.